Amphetamine Detection in Human Blood Plasma With LC_MS/MS - Wiraagni, Idha Arfianti (Jurnal Forensik dan Medikolegal Indonesia, 2019)
ABSTRACT The use of stimulants as a abused drug are very common in all over the world. One of the main stimulant that are widely used are amphetamine, because it has potent effect in increasing activity of the body and central nervous system, through the stimulation ofneurotransmitter.This research successfully performed aneffective, efficient, and simple protein precipitation extraction procedure of amphetamine from human plasma then analysed by (Liquid Chromatography Tandem Mass Spectrometry / LC-MS/MS). This method showed fast running time with minimum cost and volume of sample.The developed methodhad quite good sensitivity, specificity, and recovery for amphetamine detection in human plasma samples in the concentration more than 100 ng/mL.This method was suggested for confirmatory screening test, that are needed to make sure the presence of amphetamine in human blood plasma. Key words: amphetamine, human blood plasma, screening, LC-MS/MS